Maqasid Syariah sebagai Kritik Filosofis terhadap Dominasi Murabahah dalam Perbankan Syariah Modern: Sebuah Systematic Literature Review - Afril Afril; Syukri Iska; Ahmad Lutfi (Economics and Digital Business Review, 2025)
This study aims to philosophically analyze the dominance of the murabahah financing contract in modern Islamic banking through the perspective of Maqāṣid al-Sharī‘ah using a Systematic Literature Review (SLR) approach. A total of 15 scientific articles were selected after a rigorous screening process based on thematic relevance, methodological feasibility, and full-text availability. The results indicate that the dominance of murabahah in the financing portfolio of Islamic banks is primarily driven by profitability orientation and risk-management efficiency rather than ethical and socio-economic objectives of Islamic economics. Empirical findings reveal that murabahah significantly contributes to profit generation and financial stability in Islamic banks; however, its operational practice often deviates from the substantive nature of a genuine sale contract and drifts away from the principles of justice and public welfare. Based on a maqasid analysis, current murabahah practices have not fully reflected the higher objectives of Islamic law, particularly in relation to the protection of property (ḥifẓ al-māl), justice (‘adālah), and social balance. Therefore, this research highlights the urgency of murabahah reform through a maqasid-compliance approach as the foundation for reconstructing the paradigm of Islamic economics—toward a financial system that is not only formally sharia-compliant, but also substantively aligned with social benefit and ethical well-being.